Analisis Faktor-faktor yang Berpengaruh terhadap Audit Judgment pada Auditor yang Bekerja di Kantor Inspektorat Pemerintah Kota dan Kabupaten Se-Eks Karesidenan Madiun - Hardianto, Syaddah; Purbandari, Theresia; Mujilan, - (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2018)
This study aims to demonstrate empirically the effects of professionalism, gender, obedience pressure, experience, and the complexity of the task of the audit judgment on auditors working in the Office of the City and County Inspectorate As Ex residency Madiun. The data collection is done by spreading the questionnaire . The sample in this study was 32 ​​Auditors who worked in the Office of the City and County Inspectorate As Ex residency Madiun. The sampling technique used was purposive sampling . Hypothesis testing using multiple linear regression analysis with SPSS version 17. The results of this study prove that the gender variable positive effect on audit judgment. While variable professionalism, obedience pressure, experience, and the complexity of the task has no effect on audit judgment.